2018
DOI: 10.1016/j.cellsig.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Dictyostelium Erk2 is an atypical MAPK required for chemotaxis

Abstract: The Dictyostelium genome encodes only two MAPKs, Erk1 and Erk2, and both are expressed during growth and development. Reduced levels of Erk2 expression have been shown previously to restrict cAMP production during development but still allow for chemotactic movement. In this study the erk2 gene was disrupted to eliminate Erk2 function. The absence of Erk2 resulted in a complete loss of folate and cAMP chemotaxis suggesting that this MAPK plays an integral role in the signaling mechanisms involved with this cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 74 publications
(113 reference statements)
1
24
0
Order By: Relevance
“…Using live cell imaging, we observed that cAMP-coated beads—but not uncoated beads—induced localized signaling responses, such as accumulation of PH CRAC -GFP and ΔlimE-GFP, followed by bead engulfment ( Fig 2E and 2F ). Previous studies indicated that cAMP receptor 1 (cAR1) works mainly with Gα2Gβγ subunits [ 38 40 ], while fAR1 may couple with Gα4Gβγ subunits [ 41 43 ]. We found that cAMP-coated beads induced these localized responses with subsequent phagocytic cup formation in WT , gα4 − , and far1 − cells ( S3B Fig ) but not in car1 − , gβ − , or gα2 − cells, in which cAMP sensing is abolished ( S3C Fig ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using live cell imaging, we observed that cAMP-coated beads—but not uncoated beads—induced localized signaling responses, such as accumulation of PH CRAC -GFP and ΔlimE-GFP, followed by bead engulfment ( Fig 2E and 2F ). Previous studies indicated that cAMP receptor 1 (cAR1) works mainly with Gα2Gβγ subunits [ 38 40 ], while fAR1 may couple with Gα4Gβγ subunits [ 41 43 ]. We found that cAMP-coated beads induced these localized responses with subsequent phagocytic cup formation in WT , gα4 − , and far1 − cells ( S3B Fig ) but not in car1 − , gβ − , or gα2 − cells, in which cAMP sensing is abolished ( S3C Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…Bacteria engulfment by Dictyostelium was conducted in both suspension and adhesion cultures as previously described [ 23 , 41 ]. Overnight cultured K .…”
Section: Methodsmentioning
confidence: 99%
“…ErkB null cells are defective in both speed of movement and chemotactic orientation in a variety of folate gradients ( Schwebs et al., 2018 ), presumably reflecting cumulative effects of mis-regulation of target proteins. Null mutants in these targets present diverse movement phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The proliferative stimulation and preferred formation of fruiting bodies by EMXG could both be ascribed to the elevated cellular cAMP level as evident from Table 1. Close correlation between cell proliferation and cAMP has been reported [Schwebs et al, 2018]. Still, questions remain, for example, as to the exact action site of EMXG during D. discoideum cell cycle, its mode of action other than chemoattractant, or how EMXG facilitates the enhanced formation of aggregating foci.…”
Section: Discussionmentioning
confidence: 96%